PEMBERDAYAAN IBU POST PARTUM DENGAN PEMBERIAN MODIFIKASI SENAM NIFAS TERHADAP PENURUNANINVOLUSIO UTERI DI DESA KETROKECAMATAN KARANGRAYUNG - Doa Yupita Wulansari; Festy Mahanani Mulyaningrum; Anggita Septyani Permatasari (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: The World Health Organization (WHO) stated that in 2019, the maternal mortality rate was very high, every day approximately 810 women died from preventable causes related to pregnancy and childbirth. The most common cause of maternal death is postpartum hemorrhage, which accounts for 14 million mothers or 11.4% worldwide. In developing countries, the incidence of postpartum hemorrhage is 60% of 100 thousand mothers. deaths every year and are caused by poor labor management, especially in the 3rd stage which can cause a lot of blood loss. (Ramadhan, 2019). Method: This type of research is quantitative using a pre-experimental design with a pretest posttest approach. The sample in this study was 24 post partum mothers from June-July 2024. The sample used was total sampling, with the Wilcoxon test. Results: The difference in mean TFU before and after postpartum exercise was 8.92 with the results of the comparative test data using Wilcoxon with the help of computerization. The results were obtained with a p-value of (0.000) < ɑ (0.05). From these results it can be interpreted that the Ho hypothesis is rejected and Ha is accepted, which means that there is an influence of postpartum exercise on uterine involution in post partum mothers in Ketro Village, Karangrayung District, Grobogan Regency. Conclusion; The conclusion is that there is the effect of postpartum exercise on uterine involution of post partum mothers in Ketro Karangrayung Village.